THORACIC SURGERY Genetic basis of keloid formation in wounds after cardiac surgery - Kulawczuk, Przemysław; Czapla, Norbert; Bińczak-Kuleta, Agnieszka; Safranow, Krzysztof; Jaworska-Kulawczuk, Anna; Gajewska, Dominika; Agata, Karolina; Brykczyński, Miłosz; Bargiel, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Keloid disease is the abnormal formation of scar tissue in genetically predisposed people. Among many genes which may be related to the development of keloids, transforming growth factor beta (TGF-β1) is one of the most mentioned. It encodes cytokinin, which is responsible for the production of extracellular matrix and takes part in healing. Any abnormalities which arise during synthesis of the protein as a result of polymorphism or gene mutation may be the cause of healing disorders (scarring of the body); thus it is responsible for the development of keloids. The objective of this study is to determine the single nucleotide polymorphism of the gene TGF-β1, at the position –509(rs1800469)509, to compare the obtained results in the form of three different genotypes within the analysed group (keloids) and within the control group (healthy scars), and to analyse the correlation between obtained genotypes and the occurrence of keloid disease. Seventy-three patients after cardiac surgery with scars on their sternums were examined (22 women and 51 men) in the age group from 38 to 84 years. Two groups of patients were distinguished: 37 with keloids and 36 with healthy scars. DNA taken from patients was analysed and polymorphism C(–509)T of the gene TGF-β1 was determined. On the basis of the study it was found that the allele T in the position –509 of the gene TGF-β1 is associated with a lower risk of keloid formation regardless of age and gender.